Strategic Evolution of Ancillary Revenue Streams in Commercial Aviation: A Systematic Perspective on Business Models and Consumer Dynamics - Quadros, Rui; O’Neill, Alexandra; Marques, Mariana; Cepeda , António (Journal of Ecohumanism, 2025)
In today’s competitive aviation landscape, marked by evolving consumer expectations and economic volatility, airlines increasingly rely on ancillary revenues to sustain profitability beyond traditional fares. This study presents a systematic literature review of peer-reviewed academic sources to examine the strategic evolution and implementation of ancillary revenue mechanisms across various airline business models. It contrasts how full-service, low-cost, and ultra-low-cost carriers adopt these strategies, focusing on consumer behavior, willingness-to-pay, and regional differences in response to unbundled services. Findings highlight that successful ancillary revenue generation depends not only on cost-efficient distribution but also on dynamic pricing, service personalization, and digital integration. Airlines that embrace technological innovation—especially in pricing algorithms and tailored service offerings—consistently outperform competitors in per-passenger revenue. Moreover, the study underscores the importance of aligning revenue strategies with customer expectations to avoid eroding brand trust. By synthesizing insights across global markets, the article provides a comprehensive framework for understanding how ancillary revenues function as levers for competitive advantage, financial resilience, and strategic differentiation in modern commercial aviation.